Equilibrium Pricing in Incomplete Markets - Bizid, Abdelhamid; Jouini, Elyès (Journal of Financial and Quantitative Analysis, 2005)
Abstract Given the exogenous price process of some assets, we constrain the price process of other assets that are characterized by their final payoffs. We deal with an incomplete market framework in a discrete-time model and assume the existence of the equilibrium. In this setup, we derive restrictions on the state-price deflators. These restrictions do not depend on a particular choice of utility function. We investigate numerically a stochastic volatility model as an example. Our approach leads to an interval of admissible prices that is more robust than the arbitrage pricing interval.